Bioanalysis for plasma protein binding studies in drug discovery and drug development: views and recommendations of the European Bioanalysis Forum. (March 2014) - Buscher, Brigitte; Laakso, Sirpa; Mascher, Hermann; Pusecker, Klaus; Doig, Mira; Dillen, Lieve; Wagner-Redeker, Winfried; Pfeifer, Thomas; Delrat, Pascal; Timmerman, Philip
Plasma protein binding (PPB) is an important parameter for a drug's efficacy and safety that needs to be investigated during each drug-development program. Even though regulatory guidance exists to study the extent of PPB before initiating clinical studies, there are no detailed instructions on how to perform and validate such studies. To explore how PPB studies involving bioanalysis are currently executed in the industry, the European Bioanalysis Forum (EBF) has conducted three surveys among their member companies: PPB studies in drug discovery (Part I); in vitro PPB studies in drug development (Part II); and in vivo PPB studies in drug development. This paper reflects the outcome of the three surveys, which, together with the team discussions, formed the basis of the EBF recommendation. The EBF recommends a tiered approach to the design of PPB studies and the bioanalysis of PPB samples: 'PPB screening' experiments in (early) drug discovery versus qualified/validated procedures in drug development.